Antigen mimicry as an effective strategy to induce CSPG4-targeted immunity in dogs with oral melanoma: a veterinary trial. Issue 5 (17th May 2022) - Riccardo, Federica; Tarone, Lidia; Camerino, Mariateresa; Giacobino, Davide; Iussich, Selina; Barutello, Giuseppina; Arigoni, Maddalena; Conti, Laura; Bolli, Elisabetta; Quaglino, Elena; Merighi, Irene Fiore; Morello, Emanuela; et al.
Abstract : Background: Melanoma is the most lethal form of skin cancer in humans. Conventional therapies have limited efficacy, and overall response is still unsatisfactory considering that immune checkpoint inhibitors induce lasting clinical responses only in a low percentage of patients. This has prompted us to develop a vaccination strategy employing the tumor antigen chondroitin sulfate proteoglycan (CSPG)4 as a target. Methods: To overcome the host's unresponsiveness to the self-antigen CSPG4, we have taken advantage of the conservation of CSPG4 sequence through phylogenetic evolution, so we have used a vaccine, based on a chimeric DNA molecule encompassing both human (Hu) and dog (Do) portions of CSPG4 (HuDo-CSPG4). We have tested its safety and immunogenicity (primary objectives), along with its therapeutic efficacy (secondary outcome), in a prospective, non-randomized, veterinary clinical trial enrolling 80 client-owned dogs with surgically resected, CSPG4-positive, stage II–IV oral melanoma. Results: Vaccinated dogs developed anti-Do-CSPG4 and Hu-CSPG4 immune response. Interestingly, the antibody titer in vaccinated dogs was significantly associated with the overall survival. Our data suggest that there may be a contribution of the HuDo-CSPG4 vaccination to the improvement of survival of vaccinated dogs as compared with controls treated with conventional therapies alone. Conclusions: HuDo-CSPG4 adjuvant vaccination was safe and immunogenic in dogs with oral melanoma, with potential beneficial effects on the course of the disease. Thanks to the power of naturally occurring canine tumors as predictive models for cancer immunotherapy response, these data may represent a basis for the translation of this approach to the treatment of human patients with CSPG4-positive melanoma subtypes.